(3eLJeY GdeYdheGJ GdQbej (B/s - (3YHGS, WGQb eMehOs ((3GdbGgQI(B: s (3GdeQcR GdCUjd ddfTQ(B, s, 2004)
(3JbfjI GdeYdheGJ,GdeUWdM hGdeYLe,KhQI GdeYdheGJ heVGYaGJgG,THcI GdEfJQfJ hGdJbfjI GdQbejI,eLJeY GdeYdheGJ hGdaLhI GdQbejI,JcfhdhLjG GdeYdheGJ GdQbejIs
(3HjHdjhZQGajG U(B.161s
Keywords: (3GdGfJQfJs; (3JcfhdhLjG GdeYdheGJs; (3fXe GdeYdheGJs